PERSEPSI REMAJA TERHADAP FAKTOR PENGHAMBAT PEMANFAATAN PELAYANAN KESEHATAN REPRODUKSI DI PUSKESMAS GAMBOK KABUPATEN SIJUNJUNG - Vella Dwi Yani; Ova Emilia; Hari Kusnanto (JURNAL KESEHATAN REPRODUKSI, 2014)
PERSEPSI REMAJA TERHADAP FAKTOR PENGHAMBATPEMANFAATAN PELAYANAN KESEHATAN REPRODUKSIDI PUSKESMAS GAMBOK KABUPATEN SIJUNJUNGVella Dwi Yani, Ova Emilia, Hari KusnantoABSTRACTBackground: Reproductive health service is an important component that has to be improved globally becauseteenagers often lack basic information about reproductive health. Despite the need for reproductive health serviceonly a few teenagers utilize the service due to several constraints in having reproductive and sexual health serviceas a result of limited access to the service and negative perception about center of reproductive health service.Data of Sijunjung District Health Office Sumatera Barat show that only 20% of teenagers utilize reproductivehealth service available. Whereas cases in teenagers indicate that 9.2% of teenagers have had premarital sexualintercourse and 40% are married at teenage period (<20 years) and 10% is caused by unwanted pregnancy.Objective: To study the perception of teenagers about physical, process, economic and psychosocial factors asobstacles in the utilization of reproductive health service.Method: The study was observational with cross sectional design and descriptive quantitative approach thatused qualitative data obtained from indepth interview. Subject of the study were students of SMU 1 and 2 of 14-16 years old around the working area of Health Centers that have health service for teenagers with as many as131 respondents.Result and Discussion: Perception of teenagers about physical, process and economic factors showed that themajority had good perception so these factors were not obstacles for teenagers in utilizing reproductive healthservice. The majority of teenagers (68%) had bad perception about psychosocial factor so this was an obstacle inthe utilization of reproductive health service.Conclusion: Obstacles in the utilization of reproductive health service at the health center were caused bypsychosocial factor because of shame and unwillingness to tell the problem to staff that was considered asstrangers. Teenagers also doubted the confidentiality of the problem they told to the staff.Keywords: perception, teenagers, reproductive health, utilizationABSTRAKLatar belakang: Pelayanan kesehatan reproduksi merupakan komponen penting yang harus diperbaiki secaraglobal. Remaja sering kali kekurangan informasi dasar tentang kesehatan reproduksi. Meskipun kebutuhanpelayanan kesehatan reproduksi tinggi namun pemanfaatannya masih rendah karena berbagai hambatanmemperoleh pelayanan dan juga adanya persepsi negatif terhadap pusat pelayanan kesehatan reproduksi. Datadari dinas Kesehatan kabupaten Sijunjung Sumatera Barat menunjukkan hanya 20% remaja yang memanfaatkanpelayanan kesehatan reproduksi. Sedangkan kasus dan masalah kesehatan reproduksi menunjukkan 9,2% sudahberhubungan seks sebelum menikah, dan 40% menikah pada usia remaja (<20 tahun) serta 10% mengakibatkankehamilan tak dikehendaki.Tujuan: Untuk mempelajari persepsi remaja terhadap faktor fisik, proses, ekonomi dan psikososial untukmemanfaatkan pelayanan kesehatan reproduksi remaja.melalui wawancara mendalam.Subyek penelitian adalah siswa SMA kelas 1 dan 2 usia 14-16 tahun di wilayahkerja puskesmas sebanyak 131 responden.Hasil dan Pembahasan: Mayoritas remaja memiliki persepsi baik terhadap faktor fisik, proses, dan ekonomi. Tigafaktor bukanmerupakan penghambatmemperoleh layanan kesehatan reproduksi. Sementara itu faktor psikososialdianggap sebagai penghambat (68%) untuk memanfaatkan pelayanan kesehatan reproduksi.Kesimpulan: Hambatan pemanfaatan layanan kesehatan reproduksi adalah faktor psikososial karena malu dantidak percaya untuk menceritakan masalah pada petugas kesehatan yang tidak dikenal. Remaja juga meragukankerahasiaan masalah yang diungkapkan.Kata kunci: persepsi, remaja, kesehatan reproduksi, pemanfaatan